CITRA PEREMPUAN PADA BERITA KEKERASAN SEKSUAL: ANALISIS LINGUISTIK KORPUS - Fitriana; Nurul Fadzlin; Nabila Triana; Muh. Bahly Basri; Muhammad Ilham (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aimed to analyze the image of women in sexual violence news through a corpus linguistics approach to detik.com online news in the period 2023–2025. Using AntConc software, an analysis was conducted on the frequency, collocation, and concordance of the word